Dear Mr. Henshaw - Cleary, Beverly; Zelinsky, Paul O.; Juvenile Collection (Library of Congress) (New York Morrow, 1983)
In his letters to his favorite author, ten-year-old Leigh reveals his problems in coping with his parents' divorce, being the new boy in school, and generally finding his own place in the world.
John Newbery Medal.
Keywords: Children's literature; JUVCOL; Divorce -- Juvenile fiction; Parent and child -- Juvenile fiction; Schools -- Juvenile fiction; Imprints 20th century 1983.; Juvenile literature -- New York (N.Y.) -- 1983.